2021
DOI: 10.1186/s12879-021-06899-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of peripheral white blood cells in COVID-19 patients revealed by a retrospective cohort study

Abstract: Background Peripheral hematological changes in severe COVID-19 patients may reflect the immune response during SARS-CoV-2 infection. Characteristics of peripheral white blood cells as early signals were needed to be investigated for clarifying its associations with the fatal outcomes in COVID-19 patients. Methods A retrospective cohort study was performed and the hospitalized COVID-19 patients were recruited in wards of Sino-French New City Branch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
2
18
0
3
Order By: Relevance
“…Basophils and eosinophils, which play a greater role in other innate immune functions, such as allergic and anti-microbial responses, are nevertheless also impacted in COVID-19 [31] . In this study, we demonstrated that basophils and eosinophils levels were significantly higher in COVID-19 patients with critical disease, when compared to those with moderate diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basophils and eosinophils, which play a greater role in other innate immune functions, such as allergic and anti-microbial responses, are nevertheless also impacted in COVID-19 [31] . In this study, we demonstrated that basophils and eosinophils levels were significantly higher in COVID-19 patients with critical disease, when compared to those with moderate diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively limited data indicate depletion of basophils and eosinophils occurs in the blood in COVID-19, showing some associations with severe disease. Eosinopenia is frequent and has been linked to mortality in different settings during critical COVID-19 illness [31] , [32] . By contrast, Chen R. et al [33] found that eosinophil counts, while low at admission, ultimately rebounded in a cohort of patients who ultimately recovered from severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies reported a significant association between elevated leukocyte counts and decreased lymphocyte counts among patients with severe cases of COVID-19 compared with those with mild cases [ 15 , 29 ]. However, in our study population, a decreased leukocyte count was predictive of more severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…During the acute phase of SARS-CoV-2 infection, a decreased basophil count in the peripheral blood of patients was noted [ 123 ]. Importantly, the number of basophils was significantly reduced in patients with an unfavorable outcome relative to the values obtained for patients who recovered from COVID-19 [ 124 ]. Moreover, higher relative and absolute basophil numbers were found to negatively correlate with the risk of severe COVID-19 [ 125 ].…”
Section: Cd4 T Cells and Their Subsets In Covid-19mentioning
confidence: 99%